Feasibility and Reproducibility of Two-Dimensional Wall Motion Tracking (WMT) in Fetal Echocardiography - Enzensberger, Christian; Achterberg, Friederike; Degenhardt, Jan; Wolter, Aline; Graupner, Oliver; Herrmann, Johannes; Axt-Fliedner, Roland (Ultrasound International Open, 2017)
Objective The primary objective of this study was to determine the feasibility and reproducibility of 2-dimensional speckle tracking imaging based on the wall motion tracking (WMT) technique in fetal echocardiography. The secondary objective was to compare left and right ventricular global and segmental longitudinal peak strain values.Methods A prospective cross-sectional study was performed. Global and segmental longitudinal peak strain values of the left ventricle (LV) and right ventricle (RV) were assessed prospectively. Based on apical 4-chamber views, cine loops were acquired and digitally stored. Strain analysis was performed offline. Intra- and interobserver variabilities were analyzed.Results A total of 29 healthy fetuses with an echocardiogram performed between 19 and 37 weeks of gestation were included. Analysis was performed with a temporal resolution of 60 frames per second (fps). For both examiners, in all cases Cronbach’s alpha was>0.7. The interobserver variability showed a strong agreement in 50% of the segments (ICC 0.71–0.90). The global strain values for LV and RV were −16.34 and −14.65%, respectively. Segmental strain analysis revealed a basis to apex gradient with the lowest strain values in basal segments and the highest strain values in apical segments.Conclusion The assessment of fetal myocardial deformation parameters by 2D WMT is technically feasible with good reproducibility.
Keywords: fetal echocardiography; speckle tracking; cardiac function; wall motion tracking